HUBUNGAN KREATIVITAS SISWA DENGAN HASIL BELAJAR LISTRIK OTOMOTIF SISWA KELAS II JURUSAN TEKNIK OTOMOTIF SMK NEGERI 2 BANGKO - Adi Purwanto (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2015)
This study examines the relationship problems with the creativity of students learning outcomes automotive electrical grade II Automotive Engineering Department of SMK Negeri 2 Bangko. This is a descriptive study, which aims to obtain a picture and a clear description of the relationship with the creativity of students learning outcomes automotive electrical. Hypothesis testing using Product Moment Correlation formula Person, previously conducted tests of normality and linearity regression analysis. From the analysis carried out turned out to be a relationship with the students' creativity automotive electric learning outcomes obtained at 95% significance level with large numbers of correlation coefficient of 0.421 and creativity of the student contribution to the learning outcomes for automotive electrical 17.72%, based on the results of data analysis we can conclude that there is a relationship significantly between the creativity of students with learning outcomes automotive electrical grade II Automotive Engineering Department of SMK Negeri 2 Bangko received at significant level of 95%.